2010
DOI: 10.1158/0008-5472.can-10-0447
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression: Protein Interaction Systems Network Modeling Identifies Transformation-Associated Molecules and Pathways in Ovarian Cancer

Abstract: Multiple, dissimilar genetic defects in cancers of the same origin contribute to heterogeneity in tumor phenotypes and therapeutic responses of patients, yet the associated molecular mechanisms remain elusive. Here, we show at the systems level that serous ovarian carcinoma is marked by the activation of interconnected modules associated with a specific gene set that was derived from three independent tumor-specific gene expression data sets. Network prediction algorithms combined with preestablished protein i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
(40 reference statements)
1
28
0
Order By: Relevance
“…In the current study, we identified epigenetic dysregulation of cellular functions that complement aberrant gene and protein expression patterns in our experimental model that recapitulates disease progression (25,29,31,40). Querying the clinical relevance of these epigenetic changes with tumors in the TCGA database revealed a small number of biomarker genes potentially associated with transformation (refs.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the current study, we identified epigenetic dysregulation of cellular functions that complement aberrant gene and protein expression patterns in our experimental model that recapitulates disease progression (25,29,31,40). Querying the clinical relevance of these epigenetic changes with tumors in the TCGA database revealed a small number of biomarker genes potentially associated with transformation (refs.…”
Section: Discussionmentioning
confidence: 92%
“…For immunoprecipitation, 4 mg of sonicated DNA was incubated for 12 hours at 4 C with anti-5-methylcytosine/K4/K9/K27 monoclonal antibody; standard protocols were followed for further enrichment and hybridization (31). Genome-wide promoter methylation profiling was performed using Agilent Human Promoter CpG 244 k Array (G4492A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their ability to self-renew and Interestingly, in serum free media, sometimes CSC can differentiate into progenitor cells (House et al, 2015). A.Common features found in normal and cancer stem cells (Bapat et al, 2010) 01 Capacity for asymmetric divisions (self-renewal) thatproduces a quiescent stem cell and a dedicated progenitor and plays important role toward emerging a dangerous cell mass.…”
Section: Cancer Stem Cells and Stem Cellsmentioning
confidence: 99%
“…Most studies currently remain focused on local level networks within a set of related genes or protein expressions (Bapat et al, 2010;Kirouac et al, 2010). Yet a combination of different levels of networks can be connected to overview the whole system.…”
Section: Comprehensive Vs Focused Metabolomicsmentioning
confidence: 99%